EVALUATION THE QUALITY INDICATORS OF PEPPER HYBRID SEEDS DURING GERMINATION: Kvalitet semena paprike - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2024)
The aim of the research was to evaluate the influence of the hybrid and the medium for germination testing on indicators of pepper seed quality. The obtained results should provide an answer as to whether the application of different growing media for testing seed germination can lead to discrepancies between test results in quality indicators for hybrid seeds. Seed quality testing of three different pepper hybrids: KG 2025 F1, KG 2129 F1 and KG 2032 F1 on two different media (filter paper (TP) and substrate (S)). Statistical analysis of germination energy, total germination, diseased seedlings and dead seeds showed highly significant differences (r
Keywords: paprika, hibridi, klijavost